Maternal Hair and Neonatal Meconium to Assess Gestational Consumption and Prenatal Exposure to Drugs of Abuse and Psychoactive Drugs - Cortes, Laura; Almeida, Laura; Sabra, Sally; Muniesa, Marta; Busardo, Francesco P.; Garcia-Algar, Oscar; Gomez-Roig, Maria D. (Current Pharmaceutical Biotechnology, 2018)
Background: In the last two decades, the consumption of drugs of abuse among women of childbearing age has experienced a significant increase and results from analyses of surveys concerning maternal intake of psychoactive prescription drugs during pregnancy indicate that the rates of intake are increasing each year. Analyses of biological matrices such as maternal hair and neonatal meconium have recently been used for assessment of gestational consumption and consequent prenatal exposure to drugs of abuse in high-risk groups of women. Methods: Maternal hair and neonatal meconium were analyzed by validated chromatographic-mass spectrometric methodologies to disclose the gestational use of drugs of abuse and psychoactive prescription drugs and consequent prenatal exposure in a cohort of 513 mother-newborn dyads at the Sant Joan de Déu Barcelona Hospital, Spain, during 2012-2013. Results: A total of 3.9% women reported drugs of abuse or prescription psychoactive drug consumption at any time during pregnancy. The prevalence of gestational consumption and the consequent prenatal exposure to drugs of abuse (e.g. cannabis, cocaine and MDMA) was 1.2% in maternal hair and 0.4% in meconium; and of psychoactive prescription drugs (e.g. venlafaxine, citalopram, fluoxetine, clomipramine), was 1.7% in maternal hair and 1.2% in meconium. The prevalence of drugs of abuse and prescription psychoactive drug consumption was lower in our specific cohort of Spanish pregnant women than in other cohorts such as those from U.S. or Denmark. Conclusion: Analysis of materno-fetal matrices provides a viable alternative to study prenatal exposure to these substances and develop specific social and health intervention recommendations.
Keywords: hair sampling